CD226 gene polymorphisms are associated with non-small-cell lung cancer in the Chinese Han population - Qiu ZX; Peng Y; Li WM (Dove Medical Press, 2015)
Zhi-Xin Qiu,1,* Ying Peng,2,* Wei-Min Li1 1Department of Respiratory Medicine, 2Department of Cardiology, West China Hospital, Sichuan University, Chengdu, People’s Republic of China *These authors contributed equally to this work Background: The immunoglobulin-like glycoprotein CD226 (DNAX accessory molecule-1) represents receptor-activating cytotoxic T lymphocyte and natural killer cells taking part in tumor surveillance, the pathogenesis of inflammation, and autoimmune disorders. The aim of the present study is to analyze the association between polymorphisms rs763361 and rs727088 in the CD226 gene and their impact on the pathogenesis of non-small-cell lung cancer (NSCLC).Materials and methods: Polymerase chain reaction (PCR)-restriction fragment length polymorphisms (RFLP) were used to genotype the single nucleotide polymorphisms (SNPs) rs763361 and rs727088 of the CD226 gene in 302 NSCLC patients and 389 ethnicity matched healthy controls.Results: The frequencies of the T allele and TT genotype of rs763361 (T allele odds ratio [OR] 1.42, 95% confidence interval [CI] 1.14–1.77; TT genotype OR 2.73, 95% CI 1.70–4.39), as well as the G allele and GG genotype of rs727088 (G allele OR 1.89, 95% CI 1.50–2.39; GG genotype OR 4.62, 95% CI 2.31–9.20) in the NSCLC patients were significantly higher than that of normal controls, indicating that both of these two SNPs as risk factors were associated with NSCLC (P<0.05). Results of stratified analysis revealed that the polymorphism of rs727088 was associated with lymph node invasion and clinical stage cancer (P<0.05). However, there was no association between SNP rs763361 and clinical characteristics.Conclusion: Our results demonstrated that CD226 gene polymorphisms (T allele of rs763361 and G allele of rs727088) as risk factors were associated with NSCLC. Keywords: CD226, NSCLC, polymorphism, DNAX